PENERAPAN METODE PIECES FRAMEWORK SEBAGAI EVALUASI TINGKAT KEPUASAN PENGGUNA APLIKASI BLIBLI - Zaka Sada Kris Harefa (CV. Indie Press Edutaste, 2025)
Since the emergence of the Covid-19 pandemic, competition for e-commerce platforms has become increasingly fierce, and as a result many e-commerce businesses are currently facing internal and external opportunities and dangers. The Blibli application has received many complaints from its customers, indicating that there is still a lot that needs to be improved by Blibli to continue providing maximum service to its consumers. If this is not corrected, many consumers will switch to other e-commerce applications. This research aims to measure the relationship between System Performance Evaluation using the PIECES framework method which includes 6 variables, namely: (Performance, information, Economics, Control & Security, Efficiency, and Service) on the Blibli E-commerce Application, which aims to determine the level of System Performance Application in terms of weaknesses, strengths and analyzing what components need to be improved in performance. This research uses the PIECES framework method in analyzing data. The use of the PIECES framework method is very suitable in analyzing each system variable studied because it can provide real results on the effectiveness of the system used by the company. User satisfaction with mobile application-based services is measured using the PIECES framework to determine the level of user satisfaction with services. The results of research using the PIECES framework produced an average score of 3.88 on a Likert scale. So service users are categorized as SATISFIED with the Blibli application information system services in the Rajeg Mulya area, Tangerang district RT005 RW007.